Hubungan Panjang Berat dan Faktor Kondisi Ikan Gulamah (Johnius trachycephalus) di Perairan Sungai Barumun Kabupaten Labuhanbatu - Sayyidah Napisah; Rusdi Machrizal (Bioscientist : Jurnal Ilmiah Biologi, 2021)
Gulamah fish (Johnius trachycephalus) is one type of fish that is widely consumed by the community. Prolonged use of Gulamah fish can have an impact on population decline caused by fishing activities. The purpose of this study was to determine the relationship between length and weight and condition factors of Gulamah fish in the waters of the Barumun River, Labuhanbatu Regency, North Sumatra Province. Sampling points were determined based on information from local fishermen. The Gulamah fish were taken using a net, with a net length of 20 m and a width of 8 m. Sampling was carried out four times for three months. The Gulamah fish that have been caught are then taken to the Ecology Laboratory, Labuhanbatu University, for measuring length, weighing, and separating fish by sex and so on. The number of samples during this study caught 36 fish, with a total length of Gulamah fish of 15.7 cm to 19.7 cm respectively, where the total length of the dominant fish caught averaged 18.16 cm. Meanwhile, the weight of Gulamah fish ranges from 70 grams to 113 grams, with an average fish weight of 95.08 grams. To analyze the relationship between length and weight, the Linear Allometric Model (MAL) was used, by calculating the constants a and b through length and weight measurements. While the condition factor is calculated using a metric system based on the relationship between the length and weight of the sample fish. The results showed that the relationship between the length and weight of Gulamah fish was negative allometric, which means that the length growth of the fish was faster than the weight growth. Then the condition factor states that the Barumun River supports the growth of Gulamah fish.